Comparison of PD0348292, a selective factor Xa inhibitor, to antiplatelet agents for the inhibition of arterial thrombosis - Karnicki, Krzysztof; Leadley, Robert J., Jr.; Baxi, Sangita; Peterson, Thomas; Wysokinski, Waldemar; McBane, Robert D., II (Thrombosis and Haemostasis, 2008)
The objective of this study was to determine if orally-administered PD0348292, a direct specific factor Xa inhibitor, inhibits thrombosis following porcine carotid arterial injury comparably to aspirin or clopidogrel alone or in combination. We further sought to determine whether the antithrombotic efficacy in vivo could be predicted using an ex-vivo perfusion chamber. Oral treatments included: PD0348292 (0.4, 0.9, or 4.3 mg/kg); PD0348292 (0.4 mg/kg) plus aspirin (325 mg); aspirin; clopidogrel (75 mg); aspirin plus clopidogrel; or vehicle (n=6–10/group). Aspirin and clopidogrel were administered 27 and four hours pre-injury and PD0348292 or vehicle was administered four hours pre-injury. Both carotid arteries were crush-injured, and thrombus was measured by detection of 111In-platelets over 30 minutes. Prior to injury, the antithrombotic efficacy was assessed by ex-vivo perfusion chamber platelet deposition. PD0348292 produced dose-dependent prothrombin time (0.9- to 2.9-fold) and aPTT (1.4- to 2.5-fold) prolongations. Bleeding times were significantly prolonged in each active drug group compared to vehicle, but were not significantly different between drug groups. PD0348292 significantly inhibited arterial platelet deposition (x106/cm2) at 4.3(549 ± 1,066), 0.9 (399 ± 162) and 0.4 mg/kg (531 ± 470) compared to vehicle (2,242 ± 1,443). Aspirin (992 ± 973), clopidogrel (537 ± 483), clopidogrel plus aspirin (228 ± 66) or PD0348292 plus aspirin (558 ± 317) also significantly inhibited platelet deposition, although these values were not significantly different than with any dose of PD348292. Perfusion chamber platelet deposition correlated significantly with in-vivo anti-thrombotic response. In conclusion, PD0348292 inhibited arterial thrombosis comparable to aspirin plus clopidogrel. Perfusion chamber methodology may be useful in predicting in-vivo antithrombotic efficacy.
Keywords: Thrombosis; platelets; anticoagulants; factor Xa